2015
DOI: 10.1186/s13028-015-0169-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic modelling of in vitro activity of tetracycline against a representative, naturally occurring population of porcine Escherichia coli

Abstract: BackgroundThe complex relationship between drug concentrations and bacterial growth rates require not only the minimum inhibitory concentration but also other parameters to capture the dynamic nature of the relationship. To analyse this relationship between tetracycline concentration and growth of Escherichia coli representative of those found in the Danish pig population, we compared the growth of 50 randomly selected strains. The observed net growth rates were used to describe the in vitro pharmacodynamic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
30
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 27 publications
3
30
1
Order By: Relevance
“…The direction of change in the PD-parameter Hill coefficient among bacterial isolates with different MIC (determined under the standard conditions) of the fluoroquinolone enrofloxacin for zoonotic pathogen P. multocida in this study was similar to that reported for commensal E. coli for tetracycline8. The magnitude of the change was also remarkably similar between the two bacteria-antimicrobial systems.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The direction of change in the PD-parameter Hill coefficient among bacterial isolates with different MIC (determined under the standard conditions) of the fluoroquinolone enrofloxacin for zoonotic pathogen P. multocida in this study was similar to that reported for commensal E. coli for tetracycline8. The magnitude of the change was also remarkably similar between the two bacteria-antimicrobial systems.…”
Section: Discussionsupporting
confidence: 82%
“…Recent experimental evidence confirms this hypothesis for commensal Escherichia coli and a time-dependent antimicrobial tetracycline8. For example, larger values of the PD parameter Hill coefficient are observed for E. coli isolates with higher tetracycline MICs, compared to the isolates with lower MICs8. The value captures the steepness in relationships between an increase in the antimicrobial concentration and an increase in the PD-effect on growth of the exposed bacterial population.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Several studies modeling the development of tetracycline resistance in pigs following treatment under different scenarios have recently been published (22,(40)(41)(42). Such models have been fed with data on the growth responses of E. coli to different concentrations of tetracycline.…”
Section: Discussionmentioning
confidence: 99%